2013
DOI: 10.1093/nar/gkt195
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel methyltransferase, Bmt2, responsible for the N-1-methyl-adenosine base modification of 25S rRNA in Saccharomyces cerevisiae

Abstract: The 25S rRNA of yeast contains several base modifications in the functionally important regions. The enzymes responsible for most of these base modifications remained unknown. Recently, we identified Rrp8 as a methyltransferase involved in m1A645 modification of 25S rRNA. Here, we discovered a previously uncharacterized gene YBR141C to be responsible for second m1A2142 modification of helix 65 of 25S rRNA. The gene was identified by reversed phase–HPLC screening of all deletion mutants of putative RNA methyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 61 publications
2
87
1
Order By: Relevance
“…The six enzymes involved, Bmt2, Bmt5, Bmt6, Nop2, Rcm1, and Rrp8, have only been identified recently (12)(13)(14)(15) (8,17,18). In contrast to the majority of large subunit MTases, deletion of genes encoding modification enzymes specific to the small ribosomal…”
mentioning
confidence: 99%
“…The six enzymes involved, Bmt2, Bmt5, Bmt6, Nop2, Rcm1, and Rrp8, have only been identified recently (12)(13)(14)(15) (8,17,18). In contrast to the majority of large subunit MTases, deletion of genes encoding modification enzymes specific to the small ribosomal…”
mentioning
confidence: 99%
“…15,16 m 1 A is found in all regions of transcripts including the coding sequence (CDS), as well as 5’ and 3’ untranslated regions (UTRs). 17,18 mRNA molecules have also been found to contain m 1 A although its function is less well-known.…”
Section: Rna Modificationsmentioning
confidence: 99%
“…Primer extension was performed as per previously described protocols (Cozen et al, 2015;Sharma et al, 2013) with minor modifications. One micromole of DNA primer was 32 P-5′-terminally labeled by incubation in a final volume of 25 μl with 15 μCi γ-[…”
Section: Primer Extensionmentioning
confidence: 99%
“…Base methylation is considered to expand the structural repertoire of RNA, facilitating base stacking by increasing hydrophobicity and adjusting steric hindrance (Ishitani et al, 2008). To date, base methylation of rRNA and the genes responsible for it (Bud23, Rrp8, Nop2, Rcm1, Bmt2, Bmt5 and Bmt6) have been reported in budding yeast (Gigova et al, 2014;Peifer et al, 2013;Sharma et al, 2013;White et al, 2008). A very recent report has shown that yeast and worm homologs of human NSUN5 methylate C2278 in 25S rRNA of Saccharomyces cerevisiae and C2381 in 26S rRNA of Caenorhabditis elegans; in addition, the reduction in the levels of NSUN5 homologs decreases translational fidelity in yeast and increases the lifespan of S. cerevisiae, C. elegans and Drosophila melanogaster (Schosserer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%